THE EFFECT OF AN INTERACTIVE BOARD GAME-BASED DRILL METHOD ON THE EARLY READING ABILITY OF FIRST GRADE STUDENTS AT SDN 1 BANDORASAKULON - Sri Ayu Jannah; Widia Nur Jannah; Hanikah Hanikah (Universitas Majalengka, 2025)
This study aims to determine the effect of applying the drill method based on interactive board games on the early reading ability of first-grade students at SDN 1 Bandorasakulon, Cilimus District, Kuningan Regency. The research method used was an experimental design with a pretest-posttest model. The subjects of the study were 20 students. The research instruments consisted of an early reading ability test and observation sheets for teacher and student activities. The results showed that the implementation of the drill method based on interactive board games was carried out effectively, as evidenced by the observation results of teacher and student activities which reached 93% in the “very good” category. Students’ early reading ability improved significantly, with an average pretest score of 54.38 (3 students achieved mastery and 17 did not) increasing to 82.19 in the posttest (19 students achieved mastery and 1 did not). The Paired Sample T-Test revealed a significance value of 0.000 < 0.05, indicating that the drill method based on interactive board games had a significant effect on early reading ability. The N-Gain analysis result of 0.6428 fell into the medium category with an effectiveness of 64.28%. Therefore, this method is effective in improving the early reading ability of elementary school students.